Microbial degradation kinetics and molecular mechanism of 2, 6-dichloro-4-nitrophenol by a Cupriavidus strain. (March 2020) - Min, Jun; Xu, Lingxue; Fang, Suyun; Chen, Weiwei; Hu, Xiaoke
Abstract: 2, 6-Dichloro-4-nitrophenol (2, 6-DCNP) is an emerging chlorinated nitroaromatic pollutant, and its fate in the environment is an important question. However, microorganisms with the ability to utilize 2, 6-DCNP have not been reported. In this study, Cupriavidus sp. CNP-8 having been previously reported to degrade various halogenated nitrophenols, was verified to be also capable of degrading 2, 6-DCNP. Biodegradation kinetics assay showed that it degraded 2, 6-DCNP with the specific growth rate of 0.124 h −1, half saturation constant of 0.038 mM and inhibition constant of 0.42 mM. Real-time quantitative PCR analyses indicated that the hnp gene cluster was involved in the catabolism of 2, 6-DCNP. The hnpA and hnpB gene products were purified to homogeneity by Ni-NTA chromatography. Enzymatic assays showed that HnpAB, a FAD-dependent two-component monooxygenase, converted 2, 6-DCNP to 6-chlorohydroxyquinol with a K m of 3.9 ± 1.4 μM and a k cat / K m of 0.12 ± 0.04 μΜ −1 min −1 . As the oxygenase component encoding gene, hnpA is necessary for CNP-8 to grow on 2, 6-DCNP by gene knockout and complementation. The phylogenetic analysis showed that the hnp cluster originated from the cluster involved in the catabolism of chlorophenols rather than nitrophenols. To our knowledge, CNP-8 is the first bacterium with the ability to utilize 2, 6-DCNP, and this study fills a gap in the microbial degradation mechanism of this pollutant at the molecular, biochemical and genetic levels. Moreover, strain CNP-8 could degrade three chlorinated nitrophenols rapidly from the synthetic wastewater, indicating its potential in the bioremediation of chlorinated nitrophenols polluted environments. Graphical abstract: Image 1 Highlights: Cupriavidus sp. CNP-8 can utilize 2, 6-dichloro-4-nitrophenol (2, 6-DCNP) for growth. HnpAB catalyzes the sequential denitration and dechlorination of 2, 6-DCNP. HnpA is evolutionary close to chlorophenol but nitrophenol monooxygenases. hnpA is necessary for strain CNP-8 to utilize 2, 6-DCNP. This study fills a gap in the microbial degradation of 2, 6-DCNP. Abstract : This study fills a gap in the microbial degradation process and mechanism of 2, 6-DCNP, enhancing our understanding of the environmental fate of this pollution.